Rationale, design and objectives of two phase III, randomised, placebo-controlled studies of GLPG1690, a novel autotaxin inhibitor, in idiopathic pulmonary fibrosis (ISABELA 1 and 2). Issue 1 (21st May 2019) - Maher, Toby M; Kreuter, Michael; Lederer, David J; Brown, Kevin K; Wuyts, Wim; Verbruggen, Nadia; Stutvoet, Simone; Fieuw, Ann; Ford, Paul; Abi-Saab, Walid; Wijsenbeek, Marlies
Abstract : Introduction: While current standard of care (SOC) for idiopathic pulmonary fibrosis (IPF) slows disease progression, prognosis remains poor. Therefore, an unmet need exists for novel, well-tolerated agents that reduce lung function decline and improve quality of life. Here we report the design of two phase III studies of the novel IPF therapy, GLPG1690. Methods and analysis: Two identically designed, phase III, international, randomised, double-blind, placebo-controlled, parallel-group, multicentre studies (ISABELA 1 and 2) were initiated in November 2018. It is planned that, in each study, 750 subjects with IPF will be randomised 1:1:1 to receive oral GLPG1690 600 mg, GLPG1690 200 mg or placebo, once daily, on top of local SOC, for at least 52 weeks. The primary endpoint is rate of decline of forced vital capacity (FVC) over 52 weeks. Key secondary endpoints are week 52 composite endpoint of disease progression or all-cause mortality (defined as composite endpoint of first occurrence of ≥10% absolute decline in per cent predicted FVC or all-cause mortality at week 52); time to first respiratory-related hospitalisation until end of study; and week 52 change from baseline in the St George's Respiratory Questionnaire total score (a quality-of-life measure). Ethics and dissemination: Studies will be conducted in accordance with Good Clinical Practice guidelines, Declaration of Helsinki principles, and local ethical and legal requirements. Results will be reported in a peer-reviewed publication. Trial registration numbers: NCT03711162 ; NCT03733444 .